Number Theory: Tradition and Modernization - Zhang, Wenpeng; Tanigawa, Yoshio (Developments in Mathematics, 2006)
Positive Finiteness of Number Systems -- On a Distribution Property of the Residual Order of a (mod p)— IV -- Diagonalizing “Bad” Hecke Operators on Spaces of Cusp Forms -- On the Hilbert-Kamke and the Vinogradov Problems in Additive Number Theory -- The Goldbach-Vinogradov Theorem in Arithmetic Progressions -- Densities of Sets of Primes Related to Decimal Expansion of Rational Numbers -- Spherical Functions on p-Adic Homogeneous Spaces -- On Modular forms of Weight (6n + 1)/5 Satisfying a Certain Differential Equation -- Some Aspects of the Modular Relation -- Zeros of Automorphic L-Functions and Noncyclic Base Change -- Analytic Properties of Multiple Zeta-Functions in Several Variables -- Cubic Fields and Mordell Curves -- Towards the Reciprocity of Quartic Theta-Weyl Sums, and Beyond -- Explicit Congruences for Euler Polynomials -- Square-Free Integers as Sums of Two Squares -- Some Applications of L-Functions to the Mean Value of the Dedekind Sums and Cochrane Sums.